Genomic DNA extraction and amplification of Leishmania donovani using polymerase chain reaction (PCR) from archived, Giemsa- stained slides - A. Amarasinghe; D. Iddawela (Sri Lankan Journal of Infectious Diseases, 2021)
In Sri Lanka, diagnosis of cutaneous leishmaniasis (CL) is usually based on clinical features and direct microscopy examinations. Polymerase chain reaction (PCR) for Leishmania is usually performed on tissue samples. In this study, we extracted DNA from archived Giemsa-stained slides which were prepared from cutaneous lesions. A total number of 85 Giemsa-stained slides fixed between 2008-2017 were selected. All the slides were examined using light microscopy and the number of amastigotes in positive smears was recorded. A nested PCR was carried out to amplify the 385 bp fragment of L. donovani kinetoplast mini-circle sequence. All 40 positive slides had only 1-2 amastigotes per slide. Of these, only 20% were PCR positive. Of the 45 negative slides, only one gave positive PCR result. Further studies are required to confirm the efficacy of PCR on Giemsa-stained smears in our setting.